2008
DOI: 10.1007/s00418-008-0540-6
|View full text |Cite|
|
Sign up to set email alerts
|

Distribution of vitamin D binding protein expressing neurons in the rat hypothalamus

Abstract: We observed immunostaining for vitamin D binding protein (DBP) in rat hypothalamus. Part of the supraoptic and of the paraventricular neurons showed DBP immunoreactivity, in part colocalized with Arg-vasopressin. DBP was also observed in widespread axonal projections throughout the lateral hypothalamus, the median eminence and the posterior pituitary lobe. A portion of ependymal cells, the choroids plexus epithelium and some of the endocrine cells in the anterior pituitary lobe contained DBP immunoreactivity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Using the same antibodies, we also stained the brains of 6-month-old 5XFAD mice and observed that DBP coincides with Ab in the frontal cortex of 5XFAD mice (Figure 3b). Consistent with a previous report using same DBP antibody (H300: sc-32899; Santa Cruz Biotechnology, Santa Cruz, CA, USA), 18 DBPexpressing cells were detected in the hypothalamus of 6-month-old 5XFAD mice, demonstrating the specificity of DBP immunoreactivity (Supplementary Figure 1). Ab accumulation was not detectable in the hypothalamus of 6-month-old 5XFAD mice.…”
Section: Resultssupporting
confidence: 91%
“…Using the same antibodies, we also stained the brains of 6-month-old 5XFAD mice and observed that DBP coincides with Ab in the frontal cortex of 5XFAD mice (Figure 3b). Consistent with a previous report using same DBP antibody (H300: sc-32899; Santa Cruz Biotechnology, Santa Cruz, CA, USA), 18 DBPexpressing cells were detected in the hypothalamus of 6-month-old 5XFAD mice, demonstrating the specificity of DBP immunoreactivity (Supplementary Figure 1). Ab accumulation was not detectable in the hypothalamus of 6-month-old 5XFAD mice.…”
Section: Resultssupporting
confidence: 91%
“…The strongest immunohistochemical staining for both the receptor and enzyme was noted in the hypothalamus (and substantia nigra.). Recently, Jirikowski et al [63] studied immunostaining for vitamin D-binding protein (DBP) in rat hypothalamus. DBP was observed in widespread axonal projections throughout the lateral hypothalamus [63].…”
Section: Discussionmentioning
confidence: 99%
“…Recent discovery of vitamin D receptors in rodent [58] and human hypothalamus [59] indicates that vitamin D may affect hypothalamic function or serve as central neuroactive substance. The possibility that vitamin D deficiency contributes to AD pathology, hypothalamicdysfunction and subsequent bone loss should be explored in the future studies.…”
Section: Discussionmentioning
confidence: 99%